Studies on Certain Gastro-intestinal nematodes with special Reference to those Found in Goats - Sathianesan V (Department of Parasitology, College of Veterinary and Animal Sciences, 1980)
Life history of Triohuris globuloss has been elucidated for the fist time using kids !q as experimental animals. Both free living and parasitic stages have been described in detail with illustrations. The prepatent period of Triohuric globuloss was found to be 85-89 days. T.globulosa failed to develop in guniea pig on experimental transmission. Haematology and histopathology of trichuriacis in kids experimentally infected with T.globulosa have been studied for the first time and heavy infection with the worm was found to cause anaemia and pathology changes in cacum of the host. Prepatent period of Strongyloides napillosus in kids infected orally with 7000 larva has been determined for the first time to be 6-7 days. Neoasoais vitulorum of calves has been found to be not transferable to oat either transplacentally or orally. In gunia pigs M.Vitulorum failed to attain sexual maturity. Calves could not be infected with infected with M.vitulorum post-nataly. Oesphagostomum colubianum of goats has been found to be not transferable to calves. Prepatent period of O.colusbionum in kids infected experimentally was found to be 40 days. Comparative efficacy of 4 anthelminties viz., Oxibendazole, thiophanate, Albendazole and Parbendazole was increased by conducting treatment trials. Against monospecific infection of Trichuris globulosa in experimentally infected kids the efficacies of Oxibendazile, thiophanate, Albendazole and Parbendazole at the recommended doses of 10mg.50mg, 10mg and 30 mg/kg body weight respectively were found to be 48.6%, 41%,47.3% and 49.3% respectively. Even at double the recommended doses the anthelminations were found to be well tolerated by the kids. Oxibendazole and Albendazole at the rate of 10mg and 10mg/kg body weight respectively were found to be 100% found to be 100 % effective against colubriformise, effective against respectively were Haemonohus contortue, trichostrongylus .Thiopanate at the recommended dosage (59mg/kg body weight) was also 100% effective against all he nematodes mentioned above except Haemonous contortus against which it was only 97% effective at that dosage. Parbendazole at the recommended dosage shedule (30mg/kg body weight) was 100% effective against the nematodes with the exception of .against which only 86.6% efficacy was noticed. Against in nature nematodes in the gastro-intestinal tract Oxibendazole and Albendazole were 100% effective whereas the efficacies of P`arbendazole and thiophanate were 85% and 74% respectively at their recommended doses. In in vitro studies the anthelmintic efficacy of Oxibendasole against Haemonchus contortus was found to be superior to that of the remaining anthelminties. In ovicidal property also, Oxibendazole was better than all the others, since it was ovicidal in 6 hours after administration whereas albendazole, thiophanate and Parbendazole were ovicidal in 8 hours, 9 hour and 11 hours respectively. Albendazole was found to be superior to al the other 3 anthelmintion in their influences on the body weight gain of treated animals closely followed by Oxibendazole. Perbendazole and thiophanate were inferior to others Judging on the basis of over all efficacies Oxibendazole and Albendazole were found to be superior to thiophanate and Parbendasole. Treatment trials with Oxibendazole, Albendazole and thiophanate against gastro-intestinal nematodes of goats have not been attempted earlier than the present study.